Study of the condition and problems of providing diabetes patients with insulin preparations and means of glycemia monitoring - A. S. Nemchenko; T. M. Koba; V. M. Nаzаrkinа (The State Expert Center of the Ministry of Health of Ukraine, 2023)
DM is a global medico-social problem, characterized by threatening trends in the spread and development of complications. One of the key elements of the system of effective treatment of DM is the continuous supply of patients with hypoglycemic preparations & means of means of glycemic control. Therefore, it is advisable to investigate approaches to ensuring the availability of MT for the prevention, diagnosis & treatment of DM in different countries. The purpose of the work is to analyze the condition & problems of providing patients with the necessary pharmaceuticals & diagnostic products to achieve the appropriate level of compensation for diabetes. The research used: analysis of documents, marketing analysis, comparison, generalization, mathematical and statistical methods, graphic method. The analysis of official statistics shows a constant increase in the incidence of diabetes in the world among the population of different ages. Analysis of international experience shows significant differences in approaches to the organization of care for patients with diabetes, in particular, reimbursement of the cost of insulin therapy & glycemic control. In low- and middle-income countries, due to insufficient financing of antidiabetic measures, higher rates of mortality & disability related to complications of DM are recorded. In Ukraine, a government program for the reimbursement of sugar-lowering drugs has been introduced to increase the availability of drugs. Reimbursement is subject to 45 insulin preparations for 12 INNs (of which 18 are without copayment). According to the NHS, 226,200 patients receive insulin under PMG (since 2019, 2.27 mln prescriptions have been paid). The analysis of prescriptions shows that insulin analogues of foreign production are most often used. Based on the results of the research on the availability of modern MTs for the diagnosis and treatment of diabetes, it can be concluded that a wide range of glycemic control tools, including Continuous Monitoring Systems, are available on the domestic market. Providing patients with means of glycemic control is carried out at the expense of regional programs. The problem of providing patients with DM with the necessary medicines & medical devices requires a complex solution & coordination of central & local authorities actions. The priority direction of improving the efficiency and accessibility of medical care for patients with DM is to carry out proper OMT diagnosis & treatment of DM in order to include them in the reimbursement lists & procurement nomenclature.